2011
DOI: 10.1093/cid/cir403
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study Identifies Variations in 6p21.3 Associated With Nevirapine-Induced Rash

Abstract: We demonstrated that genetic variations in CCHCR1 are strongly associated with nevirapine-induced rash. A predictive model that includes genetic and clinical risk factors for nevirapine-associated rash might be useful in lowering the incidence of rash associated with nevirapine initiation among HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…In this study, both HLA-B*58:01 and HLA-DRB1*01:02 were independently associated with increased hepatotoxicity during NVP therapy [29]. In relation to rash reaction, a GWAS study conducted in Thai population has recently reported that genetic variations within CCHCR1 (rs1265112) on chromosome 6p12.3 are strongly associated with NVP-induced rash [30].…”
Section: Cyp2b6-g516gg (Common Genotype)mentioning
confidence: 53%
“…In this study, both HLA-B*58:01 and HLA-DRB1*01:02 were independently associated with increased hepatotoxicity during NVP therapy [29]. In relation to rash reaction, a GWAS study conducted in Thai population has recently reported that genetic variations within CCHCR1 (rs1265112) on chromosome 6p12.3 are strongly associated with NVP-induced rash [30].…”
Section: Cyp2b6-g516gg (Common Genotype)mentioning
confidence: 53%
“…Then, bioinformatics was applied to survey the patients' genomes for markers of genetic variation [68]. A strong association between HLA-B*3505 and nevirapine-induced skin rash was found, and variations in the CCHCR1 gene associated with nevirapine-induced skin rash also identified [69], which may provide a novel insight into the pathogenesis of drug-induced rash in the HIV-infected population [36]. A non-profit health network in U.S. has recently suggested testing HLA-B*3505 before nevirapine prescription in Thai descent based on this finding [70].…”
Section: Thailand's Hiv-1 Pharmacogenomics Projectmentioning
confidence: 99%
“…Using 361 multiethnic samples including African (YRI), European (CEU), Chinese (CHB) and Japanese (JPT) samples, de Bakker et al 2 produced a high-resolution HLA and SNP haplotype map in the extended human MHC region (26)(27)(28)(29)(30)(31)(32)(33)(34) Mb of chromosome 6). The study elucidated detailed LD structures in this region and provided information about the correlation between HLA alleles and SNPs.…”
Section: Introductionmentioning
confidence: 99%